(untitled) - Lucélia Nobre Carvalho; Luana Fidelis; Rafael Arruda; André Galuch; Jansen Zuanon (Neotropical Ichthyology, 2013)
Floating litter banks are an ephemeral habitat consisting of branches, twigs, flowers, seeds, and fruits that are trapped on the stream water surface by a variety of retention mechanisms. These heterogeneous materials form a deep layer of dead plant matter that is colonized by a variety of organisms, including fish that forage on the aquatic macroinvertebrates found in this unique habitat. In this study, we aimed to characterize which fish species occupy the floating litter banks and their trophic characteristics, as well as determine if fish assemblage composition and species richness can be predicted by the size of the floating litter banks. Fish sampling was conducted in five rivers located in the Amazon basin. Of the 31 floating litter banks sampled that contained fish, 455 individuals were recorded and were distributed within 40 species, 15 families and five orders. Siluriformes were the most representative order among the samples and contained the largest number of families and species. The fish fauna sampled was mainly composed of carnivorous species that are typically found in submerged litter banks of Amazonian streams. The fish assemblage composition in the kinon can be predicted by the volume of the floating litter banks using both presence/absence and abundance data, but not its species richness. In conclusion, kinon banks harbor a rich fish assemblage that utilizes this habitat for shelter and feeding, and may function as a refuge for the fishes during the peak of the flooding season. Bancos de folhiço flutuantes são habitats efêmeros constituídos de troncos e galhos de árvores, flores, sementes e frutos retidos por uma variedade de mecanismos. Estes materiais formam uma camada espessa de matéria vegetal morta, que é colonizada por diferentes organismos, incluindo peixes que se alimentam de macroinvertebrados aquáticos presentes neste habitat. Nosso objetivo foi caracterizar as espécies e características tróficas dos peixes que ocupam esses bancos de folhiço flutuantes, bem como determinar se a composição da assembleia de peixes e a riqueza de espécies podem ser previstas pelo tamanho dos bancos. A amostragem dos peixes foi realizada em cinco rios da bacia amazônica. Dos 31 bancos de folhiço flutuantes amostrados que continham peixes, foram registrados 455 indivíduos distribuídos em 40 espécies, 15 famílias e cinco ordens. Siluriformes foi a ordem mais representativa, com o maior número de espécies e famílias. A fauna de peixes coletados foi composta principalmente por espécies carnívoras, que geralmente são encontrados em bancos de folhiço submersos de igarapés amazônicos. A composição das assembleias de peixes do 'kinon' pode ser prevista pelo volume desses bancos de liteira flutuante, tanto utilizando dados de presença/ausência quanto de abundância, mas não de riqueza de espécies. Em conclusão, os bancos de folhiço flutuante abrigam uma rica assembleia de peixes, que utilizam esse habitat como local de abrigo e de alimentação, e podem funcionar como refúgio para a ictiofauna dos bancos de folhiço submerso durante a estação chuvosa.